Characterization of quantitative and functional innate immune parameters in HIV-1-infected Colombian children receiving stable highly active antiretroviral therapy (2008)
ABSTRACT:Background: The immunological benefits of highly active antiretroviral therapy (HAART) in HIV-1-infected children include reconstitution of CD4+ T-cell count and functional activity. The effect of HAART on innate immune cells has not been well established.Aim: To characterize innate immune responses in HAART-treated HIV-1-infected children. Patients and methods: 23 HIV-1-infected children on stable HAART and 23 uninfected children were evaluated. The frequency of innate immune cells in peripheral blood was determined by flow cytometry and functional activity was evaluated using Toll-like receptor agonists. Results: Compared with uninfected children, HAART-treated HIV-1-infected children exhibited a significant decrease in the frequency of plasmacytoid dendritic cells and natural killer and T-cell receptor (TCR)-invariant CD1d-restricted T cells. This deficiency of innate immune cells was observed mainly in children with detectable viral load. We also compared the magnitude of the quantitative restoration of those cells comparing HIV-1-infected children with HIV-1-infected adults and found a partial effect of HAART on immune restoration that was independent of age. In both pediatric and adult subjects Toll-like receptor agonists induced expression of costimulatory molecules and production of proinflammatory cytokines by dendritic cells. Peripheral blood mononuclear cells of HIV-1-infected children produced significantly reduced amounts of interferon-alpha compared with uninfected children.Conclusions: HAART administration to HIV-1-infected children does not lead to a complete increase of circulating innate immune cells, particularly in patients with incomplete suppression of HIV.